Crude Oil Spillage and the Impact of Drilling Processes on the Soil at Rumaila Oil Field- Southern Iraq - Khwedim, Kareem (Iraqi Journal of Science, 2022)
The demand on energy sources throughout the world have led to an increase in the production processes of crude oil which is considered to be the main source of energy, without considering the impact on the environment. The objective of this study is to evaluate the environmental impact of drilling processes and crude oil spillage on soil in the Rumaila oil field, Basra, Southern Iraq. An investigation was undertaken to determine the content of Polycyclic Aromatic Hydrocarbons (PAHs) and heavy metals in the soil. Ten soil samples were collected near oil wells and analyzed. The results showed a high concentration of PAHsin the soil, particularly (Acenaphthene, Fluorene, Anthracene, Fluoranthene and Pyrene) due to crude oil spillage. The heavy metals content (i.e. As, Co, Cr, Cu, Fe, Ni, Pb, V and Zn) and (B) of the analysed soil samples were compared with one standard soil sample taken from an urban area far from the pollution sources as a background. High concentrations of Co, Cr, Ni, Pb, V and B were observed in all soil samples, and therefore, exceeded the international standard limits in soil. This study documented high concentration of PAHs and heavy metals in the chosen area.